Optimizing Product Marketing at Pawon Cempaka MSMEs: A Local Brand Development Strategy: Optimalisasi Pemasaran Produk pada UMKM Pawon Cempaka: Strategi Pengembangan Brand Lokal - Shaafi Abidah; Mochamad Rizal Yulianto (Procedia of Social Sciences and Humanities, 2026)
General Background Small and medium enterprises in the culinary sector drive regional economic growth. Specific Background Pawon Cempaka in Malang faces challenges regarding low digital platform visibility and limited market reach. Knowledge Gap However, practical integration between digital marketing and local community promotion remains insufficiently explored in local culinary contexts. Aims This study analyzes digital marketing strategies, identifies operational hurdles, and proposes integrated solutions for local brand sustainability. Results Findings reveal that while food delivery platforms expand potential reach, offline community-based marketing yields higher immediate conversion, whereas sales sustainability requires continuous product differentiation. Novelty This research highlights a hybrid marketing framework combining offline community engagement with digital channels tailored for emerging culinary businesses. Implications Consequently, culinary small businesses must blend digital promotion with product innovation and community partnerships to maintain long-term market competitiveness. Keywords: Brand Awareness, Culinary Product Innovation, Digital Marketing Strategy, Local Brand Development, Small Medium Enterprises Key Findings Highlights Offline community-based promotions generate higher conversion rates for new culinary businesses than online delivery platforms. Continuous product and packaging innovation is essential to prevent sales decline caused by market competition. Combining digital food platforms with local community collaboration strengthens overall brand sustainability.